Validation of a lightning protection system for a fusion-welded thermoplastic composite wind turbine blade tip. Issue 1 (February 2022) - Murray, Robynne E; Plumer, Andy; Beach, Ryan; Broome, Peter
Fusion welding for thermoplastic composite wind turbine blades is being investigated as a replacement for adhesives in bond lines to reduce manufacturing time and cost and to promote ease of recyclability. Resistance welding uses an electrically conductive material, such as carbon fiber, embedded in the bond line to heat the joining surfaces and fuse them together under pressure. One main challenge with fusion joining for large wind blades is the ability to use this conductive heating element in the bond line while still protecting the blade from the catastrophic effects of a lightning strike. This paper outlines the design and manufacturing of a lightning protection system for a 5-m-long thermally welded blade tip. The outcomes of high voltage and high current lightning testing applied to the 5 m blade tip show that the proposed design was able to protect the fusion welded bond lines from significant lightning damage.